PENGARUH KUALITAS PELAYANAN BENGKEL TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN - Taufan, Sonny; Akhsan, Muhamad Nur (ULTIMA Management, 2023)
This research was conducted at PT Setiajaya Mobilindo - Setiajaya Toyota Depok, with the aim of Knowing the influence of workshop service quality on customer satisfaction Knowing the influence of customer satisfaction on customer loyalty and Knowing the level of quality of workshop service provided on customer loyalty through PT Setiajaya Mobilindo - Setiajaya Toyota Depok customer satisfaction. The population in this study were all customers at PT Setiajaya Mobilindo - Setiajaya Toyota Depok Pekanbaru. Using the Slovin formula and accidental sampling technique, 161 selected samples were obtained. The research method was carried out descriptively and quantitatively, using simple regression testing techniques and the data was then processed using the IBM SPSS Statistics 26 program. With this research, research estimates were produced as to whether service quality has an effect on customer satisfaction and also whether customer satisfaction and service quality have an impact. influence on customer loyalty.